ETIKA DAKWAH (Telaah Terhadap Fenomena Perkembangan Dakwah Masa Kini) - Rasyid, Muh. Haras; Badwi, Ahmad (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2025)
The main theme of this paper is the issue of da'wah ethics, related to the development of da'wah in Indonesia today. Da'wah that we understand as an invitation to do good and prevent evil is highly recommended in Islamic teachings, as in the Qur'an and hadith. By using analysis through observation of the phenomena that arise from the practices of da'wah in society today, it provides a clue that the development of da'wah in addition to the appearance of progress as a positive thing, but the reality in practice, there are also things that can be considered negative. Especially that can be considered negative, because there are some or unscrupulous da'i or muballig who preach is considered not in accordance with the ethics of da'wah. In general, preachers are considered to deviate from the ethics of da'wah, in addition to the impression that their words and actions do not match, they also deliberately utter many words that are inappropriate according to the social ethics that grow and are obeyed in society, the ethics of state law and ethics originating from Islamic teachings.